Training on Making Digital Learning Media to Improve Motivation and Learning Outcomes of Elementary School Students for Teachers SD Negeri 068332 Medan - Saib Suwilo; Elvina Herawati; Mimmy Sari Syah Putri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Learning media today is one thing that is very important in supporting the success of the student learning process at school. Monotonous learning only in the form of narration makes students bored with the learning process, so teachers must change student learning methods to make it more interesting and of course to improve the learning outcomes of these students. The demands of the times have required teachers to understand digital learning media. Of course, it is accompanied by the teacher's ability to mix and design in such a way that the learning process and the material presented can be in line and not boring. The learning process is basically a communication process through interaction between teachers and students. In the communication process the message is conveyed by the teacher to the recipient of the message or student. In the context of learning in the classroom, the message conveyed can be in the form of teaching materials delivered verbally (oral and written) and / or nonverbally (gestures). Not only teachers as communicators, learners can also act as communicators or messengers. This can happen in the midst of an increasingly modern learning system. Teachers are no longer the only source of learning, but learners can explore themselves to dig up information from various sources and communicate it in the learning process. Thus, there will be two-way communication or multiways traffic communication. Learning with both communication models requires the role of learning media to increase the effectiveness of achieving goals or competencies.